Visual communication : understanding images in media culture - Aiello, Giorgia; Parry, Katy, 1973- (London : SAGE Publications Ltd, 2020)
Visual Communication: Understanding Images in Media and Culture provides a theoretical and empirical toolkit to examine implications of mediated images. It explores a range of approaches to visual analysis, while also providing a hands-on guide to applying methods to students' own work. The book: Illustrates a range of perspectives, from content analysis and semiotics, to multimodal and critical discourse analysis Explores the centrality of images to issues of identity and representation, politics and activism, and commodities and consumption Brings theory to life with a host of original case studies, from celebrity videos on Youtube and civil unrest on Twitter, to the lifestyle branding of Vice Media and Getty Images Shows students how to combine approaches and methods to best suit their own research questions and projects An invaluable guide to analysing contemporary media images, this is essential reading for students and researchers of visual communication and visual culture.
Includes bibliographical references and index.
Description based on XML content.
Keywords: Visual communication; Visual analytics; Social media and society